Assessing the Contribution of Hajj Savings Customers and Hajj Savings Deposits to Third-Party Fund Growth - Windy Adinda Sari; Tuti Anggraini; Nurul Inayah (International Conference on Islamic Economic (ICIE), 2026)
Third-Party Funds (TPF) are the primary funding source for Islamic banks, yet the increasing number of customers does not always correspond to optimal growth in TPF. Likewise, although Hajj Savings based on the Wadiah Yad Dhamanah contract have become an increasingly popular savings product, empirical evidence regarding their contribution to TPF growth remains limited, particularly in regional Islamic banks. This study aims to examine the contribution of the number of customers and Hajj Savings funds under the Wadiah Yad Dhamanah contract to the growth of Third-Party Funds at PT Bank Sumut Sharia Sub-Branch Office Panyabungan. This study employed a quantitative associative approach using quarterly secondary data for the 2021–2025 period. Data were analyzed using multiple linear regression with SPSS. The findings reveal that the number of customers and Hajj Savings funds each have a positive and significant effect on Third-Party Funds, and jointly explain 85.3% of the variation in TPF growth. The study contributes empirical evidence that optimizing Hajj Savings products, alongside customer growth, can strengthen sustainable Third-Party Fund mobilization strategies in regional Islamic banking institutions.